School Networks and Telematics Services:perspectives of international co-operation in the Mediterranean - Christos Bouras; G Tsakarissianos (Telecommunication Information Management Journal, Volume 2, Issue 6, 2001)
The forthcoming ‘Information Society’ is expected to transform radically the way of communicating knowledge and expertise. The application of ICT for educational purposes should be aimed to improve the education process in terms of pedagogical methodologies, school infrastructure, human resources development and organisational restructuring, in order to efficiently absorb and utilise the technological developments. New learning paradigms have already emerged giving emphasis to the communication and collaborative aspects of the learning process. Self-supported and collaborative learning is expected to transform the traditional educational activities (teacher-centred model) and promote flexibility, reflection and group interaction.